Revision of the Neotropical termite genus Orthognathotermes Holmgren (Isoptera: Termitidae: Termitinae) - Da Rocha, Mauricio Martins; Cancello, Eliana M. (Zootaxa, 2009)
This is a taxonomic revision of the Neotropical genus Orthognathotermes Holmgren, 1910 (Termitidae, Termitinae), previously with nine species: O. aduncus, O. brevipilosus, O. gibberorum, O. heberi, O. humilis, O. insignis, O. macrocephalus, O. orthognathus and O. wheeleri. We redescribe these species and describe six new species: O. longilamina sp. nov., O. mirim sp. nov., O. okeyma sp. nov., O. pilosus sp. nov., O. tubesauassu sp. nov., and O. uncimandibularis sp. nov., based on soldiers and, when possible, imago castes along with the first description of imagos of O. wheeleri and O. heberi. We present a key for soldier identification and distribution maps for all species.